Designing electronic equipment on the basis of standard mechanical structures using internet resources - Karlangach A. P. (Tekhnologiya i Konstruirovanie v Elektronnoi Apparature, 2016)
The author proposes a method to design electronic equipment based on functional-node design method that involves the use of 2D- and 3D- models mechanical structures for electronic equipment as a way to reduce development time and errors when creating design documentation for electronic equipment. At present, most areas of science and technology are computerized, more problems in designing electronic equipment are dealt with using computer-aided design (CAD) and Computer-aided manufacturing (CAM) to reduce the time required for development and manufacturing of electronic equipment. Development of design documentation also requires a more effective approach, because the less the time for development of the design documentation is, the faster the developed device will go into production. The aim of the study is to develop a method of designing electronic equipment using 2D and 3D models of standard mechanical structures for electronic equipment using Internet resources. Based on the presented methods is an example of designing a device from standard bearing structures. Compared with traditional technology, the method of designing electronic equipment using standard parts has the following advantages: - reduces time and improves quality of development through the use of existing design documentation; - accelerates the implementation and introducing into production processes; - increases unification of design solutions.